Association of CD14 −159 (−260C/T) polymorphism and asthma risk: an updated genetic meta-analysis study. Issue 39 (September 2016) - Wang, Duan; Yang, Yang; Xu, Jin; Zhou, Zong-Ke; Yu, Hai-Yang
Abstract: Background: It has been reported that the cluster of differentiation 14 ( CD14 ) gene −159C/T variant may be associated with asthma risk. However, some studies yielded conflicting results. Therefore, a comprehensive meta-analysis was designed to assess the precise association. Methods: A systematic search in PubMed, Embase (Ovid), China National Knowledge Internet (CNKI), and Wan fang databases was conducted up to August 15, 2015. Odds ratio (OR) and 95% confidence interval (CI) were used to pool the effect size. We used I 2 to assess heterogeneity, and a funnel plot and Egger test to assess publication bias. Results: In total, 34 studies involving 15, 641 subjects were included in this meta-analysis. There was a statistically significant association between CD14 −159C/T polymorphism and asthma risk observed in dominant model (TT+TC vs CC: OR = 0.86, 95% CI = 0.77–0.97, P = 0.012) and codominant model (TC vs CC: OR = 0.88, 95% CI = 0.78–0.99, P = 0.035) in adults. However, there may be no significant association between CD14 159C/T and atopic and nonatopic asthma risk. Conclusion: In summary, the overall results suggested that the CD14 −159C/T variant may decrease the risk of asthma susceptibility in adults. However, no significant association between CD14 159C/T and atopic and nonatopic asthma susceptibility was identified. More studies with larger sample size are needed to validate the findings from this study.